Persepsi Guru tentang Dampak Sertifikasi terhadap Kualitas Mengajar dan Kesejahteraan - Cut Kumala Sari; Melva Rossi; Sri Sundari (Mutiara Pendidikan dan Olahraga, 2025)
This study aims to uncover teachers' views on the impact of certification on the quality of teaching and their welfare. Teacher certification is a government program that aims to improve the quality of education through professional recognition of teachers who have met certain competency standards. This study uses a qualitative approach with a descriptive method through a literature review of various journals and relevantiliteratureisources. Theiresultsiof theianalysis show that a number of teachers experienced an increase in pedagogical competence, self-confidence, and teaching enthusiasm after obtaining certification. However, some others felt that the impact of certification had not been felt too much, especially due to the increasing administrative burden and the lack of further training. On the other hand, certification also provides benefits to teacher welfare through the provision of professional allowances, although there is still inequality in its distribution. This study highlights the importance of continuous evaluation of certification policies, accompanied by reducing administrative burdens and strengthening post-certification training to support teacher professionalism and welfare as a whole.